Developing self and self-concepts in early childhood education and beyond - Raban-Bisby, Bridie (Emerald points., 2020)
It is widely accepted that interactions between adults and infants change over time and babies play a dynamic role in their interactions with those who care for them. Acknowledging that their sense of self is moulded by these experiences, and reflected in their own behaviours later in life, this book focuses on the development of an infant's sense of self from the moment of birth, into school, and beyond. In the first part of the monograph, the author weaves together both theoretical speculation and empirical research on the topic. Studies from across the last century are tracked and reinforced with 21st century contemporary research. Moving on from this foundation, the second section presents an observation study of four three-year old children in their homes and first term in school, providing a real-life practical illustration of the theoretical background. Drawing on analysis of children in their home environments and in school, including transcripts of conversations engaged in at home, and notes based on classroom observations, the author presents a cutting-edge insight into the adjustment and adaptation of the study participants' first experience of school, reflected against the background of their home lives.